2017
DOI: 10.1542/peds.2017-1100
|View full text |Cite
|
Sign up to set email alerts
|

Observational Assessment in the Febrile Infant

Abstract: Opinions expressed in these commentaries are those of the author and not necessarily those of the American Academy of Pediatrics or its Committees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The high sensitivity of the YOS to predict patients with serious illness in our study was also comparable with that reported in other studies [4,6,12,15]. Three of these were conducted in developed or semi-developed countries (2 studies in USA, 1 study in UK and 1 in Turkey) and included relatively older children (<24 months or <36 months) than those included in other studies (<60 days) [3,17]. These findings indicate that the YOS may be more useful in children aged >3 months rather than in younger infants.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The high sensitivity of the YOS to predict patients with serious illness in our study was also comparable with that reported in other studies [4,6,12,15]. Three of these were conducted in developed or semi-developed countries (2 studies in USA, 1 study in UK and 1 in Turkey) and included relatively older children (<24 months or <36 months) than those included in other studies (<60 days) [3,17]. These findings indicate that the YOS may be more useful in children aged >3 months rather than in younger infants.…”
Section: Discussionsupporting
confidence: 90%
“…The difference with our results may be attributable to a younger cohort compared to that in our study. Indeed, the YOS has been reported to have limited diagnostic efficacy when evaluating febrile infants in the first 2-3 months of life [3]. That is because this group has less-developed repertoire of responses to stimuli compared with older children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Yale Observation Scale (YOS) is an illness severity scale using simple observations which is easily applicable. [5][6][7][8][9][10][11][12] The objective of this study was to observe the efficacy of YOS in detecting serious bacterial infection in febrile children 1 to 36 months of age. Permission was taken from hospital authority.…”
Section: Introductionsmentioning
confidence: 99%